Evaluating Soil Fertility and Plant Nutrient Status of Lemon (Citrus Limon L.) Orchards in the North-Eastern Region of Bangladesh (Journal of Biodiversity Conservation and Bioresource Management, 2023)
Soil (0 to 15 cm and 15 to 30 cm depth), leaf and fruit samples were collected from seventeen orchards of lemon (Citrus limon L.) from different locations of Habiganj district to evaluate the physicochemical properties, nutrient status of soil, and nutrient concentrations in lemon leaves and fruits. The soil was found to vary pH from extreme to medium acidic (3.9 to 6.0), organic matter content 0.63 to 1.71% at 0 to 15 cm and 0.16 to 1.42% at 15 to 30 cm depth. Electrical Conductivity was found non-saline in nature which was 37.9 to 100.1 μS/cm at 0 to 15 cm and 25.1 to 69.0 μS/cm at 15 to 30 cm depth. The dominant soil textural class was sandy clay loam. The total N, P, K and S in soils were found 0.038 to 0.085%, 0.024 to 0.071%, 0.022 to 0.144%, and 0.040 to 0.294% at 0 to 15 cm depth, respectively and 0.012 to 0.076%, 0.024 to 0.056%, 0.012 to 0.139%, and 0.016 to 0.333% at 15 to 30 cm depth, respectively. Available N was found 20.37 to 67.90 mg/kg at 0 to 15 cm and 20.37 to 74.69 mg/kg at 15 to 30 cm depth. Major soil samples were found low in available phosphorous, 0.35 to 66.95 mg/kg at 0 to 15 cm and 0.83 to 29.19 mg/kg at 15 to 30 cm depth. Available sulphur was also found low in concentration, 4.62 to 68.48 mg/kg at 0 to 15 cm and 2.10 to 15.54 mg/kg at 15 to 30 cm depth. The exchangeable K+, Ca2+ and Mg2+ in soils at 0 to 15 cm depth were found 0.040 to 0.221 meq/100g, 0.002 to 0.046 meq/100g and 0.017 to 0.042 meq/100g, respectively and at 15 to 30 cm depth these were found from 0.025 to 0.097 meq/100g, 0.003 to 0.054 meq/100g, and 0.016 to 0.050 meq/100g, respectively. The concentrations of total N, P, K and S in leaf were 1.198 to 2.659%, 0.500 to 0.778%, 0.112 to 0.246% and 0.010 to 0.133%, respectively. The concentrations of total N, P, K and S in fruit were 0.760 to 1.549%, 0.250 to 0.611%, 0.107 to 0.190% and 0.005 to 0.031%, respectively. The present findings illustrated the low to medium soil fertility status under the lemon plantation in the north-eastern region of Bangladesh and growers could be recommended to plant lemons after applying soil amendments to improve the physico-chemical properties of soils in the north-eastern region of Bangladesh.J. Biodivers. Conserv. Bioresour. Manag. 2023, 9(1): 69-78